2020
DOI: 10.1002/jbmr.4485
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Controls Bone Homeostasis by Regulating Osteogenic/Adipogenic Fate of Skeletal Stem/Progenitor Cells in Mice

Abstract: Skeletal stem/progenitor cells (SSPCs) can differentiate into osteogenic or adipogenic lineage. The mechanism governing lineage allocation of SSPCs is still not completely understood. Hedgehog (Hh) signaling plays an essential role in specifying osteogenic fate of mesenchymal progenitors during embryogenesis. However, it is still unclear whether Hh signaling is required for lineage allocation of SSPCs in postnatal skeleton, and whether its dysregulation is related to age-related osteoporosis. Here, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…These two Hh ligands might activate Hh signaling in the growth plate chondrocytes of juvenile mice. In agreement with this prediction, activity of Hh signaling was indeed detected in the growth plate chondrocytes in juvenile and adult mice (Shi et al, 2017;Haraguchi et al, 2018;Newton et al, 2019;Zhang et al, 2022), implying a direct requirement of Hh signaling in chondrocytes. Consistently, pharmacological inhibition of Hh signaling during or after SOC formation led to premature closure of long bone growth plates (Kimura et al, 2008), confirming the functional significance of Hh signaling in epiphyseal growth plate maintenance during juvenile growth.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…These two Hh ligands might activate Hh signaling in the growth plate chondrocytes of juvenile mice. In agreement with this prediction, activity of Hh signaling was indeed detected in the growth plate chondrocytes in juvenile and adult mice (Shi et al, 2017;Haraguchi et al, 2018;Newton et al, 2019;Zhang et al, 2022), implying a direct requirement of Hh signaling in chondrocytes. Consistently, pharmacological inhibition of Hh signaling during or after SOC formation led to premature closure of long bone growth plates (Kimura et al, 2008), confirming the functional significance of Hh signaling in epiphyseal growth plate maintenance during juvenile growth.…”
Section: Introductionmentioning
confidence: 53%
“…We previously showed that Hh signaling was activated in the chondrocytes of epiphyseal growth plates from 2-and 12-monthold mice (Zhang et al, 2022). To further characterize Hhresponsive cells in the epiphyseal growth plates during postnatal skeletal growth, we first examined the expression of Gli1, a transcriptional target of Hh signaling activity in juvenile and adult mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations